2021
DOI: 10.3390/nu14010148
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response to Daytime Dry Fasting in Bahá’í Volunteers—Results of a Preliminary Study

Abstract: Each year in March, adherents of the Bahá’í faith abstain from eating and drinking from sunrise to sunset for 19 days. Thus, Bahá’í fasting (BF) can be considered as a form of daytime dry fasting. We investigated whether BF decreased energy expenditure after a meal and whether it improved anthropometric measures and systemic and tissue-level metabolic parameters. This was a self-controlled cohort study with 11 healthy men. We measured anthropometric parameters, metabolic markers in venous blood and pre- and po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In a laboratory study with a subsample of the one presented here, we were able to show that fluid balance remained stable in most individuals (Koppold-Liebscher et al, 2021), and fat metabolism was enhanced (Mähler et al, 2021). Studies have shown that religion and spirituality do influence health behaviours (Litalien et al, 2022).…”
Section: Bahá'í Fastingmentioning
confidence: 48%
See 1 more Smart Citation
“…In a laboratory study with a subsample of the one presented here, we were able to show that fluid balance remained stable in most individuals (Koppold-Liebscher et al, 2021), and fat metabolism was enhanced (Mähler et al, 2021). Studies have shown that religion and spirituality do influence health behaviours (Litalien et al, 2022).…”
Section: Bahá'í Fastingmentioning
confidence: 48%
“…Written informed consent was obtained from all participants prior to study entry and a detailed explanation of the main study design is found in our published study protocol (Koppold-Liebscher et al, 2021). The outcomes of the clinical and laboratory findings have been reported elsewhere (Koppold-Liebscher et al, 2021;Mähler et al, 2021), as have been the qualitative findings (Ring et al, 2022) and some quantitative findings (Demmrich et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Sleep disorder is a wide risk factor for the onset of mental illness. The Baha'i Fast (BF) is a religious fast of fasting and abstaining from food and drink during daylight hours for 19 consecutive days every year in March (Mähler et al, 2021). Ring's research suggests that Bahá'í fasting appears to enhance participants' mindfulness and well-being, lower stress levels, and reduce fatigue.…”
Section: Sleepmentioning
confidence: 99%